2008
DOI: 10.1097/coc.0b013e318173a536
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Escalation Study of Aerosolized Sargramostim in the Treatment of Metastatic Melanoma

Abstract: Objectives-Early testing of aerosolized sargramostim therapy demonstrated anecdotal clinical responses in patients with metastatic melanoma associated with emergence of systemic anti-tumor immunity. In order to improve the clinical and immunological efficacy of therapy without compromising patient safety, we performed a further dose escalation trial in patients with metastatic melanoma.Methods-We conducted a dose-escalation clinical trial of HLA-A2 + patients with metastatic melanoma to the lung treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…GM-CSF inhalation therapy did not increase serum levels of GM-CSF autoantibody, which is of importance to the autoimmune basis of the disorder in patients with the common autoimmune form of the syndrome (2). Our results are supported by other studies indicating the safety of inhaled GM-CSF therapy in humans (28,29). A small decrease in neutrophil counts was observed during treatment but counts remained within the normal range.…”
Section: Discussionsupporting
confidence: 82%
“…GM-CSF inhalation therapy did not increase serum levels of GM-CSF autoantibody, which is of importance to the autoimmune basis of the disorder in patients with the common autoimmune form of the syndrome (2). Our results are supported by other studies indicating the safety of inhaled GM-CSF therapy in humans (28,29). A small decrease in neutrophil counts was observed during treatment but counts remained within the normal range.…”
Section: Discussionsupporting
confidence: 82%
“…Overall survival was similar to that described in multiple previous studies (1-6, 8, 9.). Our study again provided proof of principle that inhalation therapy for malignancy is a feasible and non-toxic route of administration of GM-CSF, which has shown some activity in other human tumor models (27). Doses of GM-CSF of 1750 μg twice daily however have not been previously administered to pediatric and adolescent patients.…”
Section: Discussionsupporting
confidence: 56%
“…However, no GM-CSF dose was capable of inducing antitumor immunity in the majority of patients. However, 5 patients developed an immune response to one or more melanoma specific antigens (27). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a previous investigation (NCCTG study) has consisted to perform a dose-escalation clinical trial with aerosolized sargramostim in HLA-A2 patients with metastatic melanoma to the lung ( n = 40). The data showed that the toxicity was acceptable for all tested doses and the greatest increase in antitumor T-cell immune responses was achieved at the highest doses [77]. Then, a hypothesis-generating study was conducted to evaluate the safety and efficacy of prolonged administration of sargramostim as surgical adjuvant therapy in patients with melanoma at high risk of recurrence ( n = 98) [78].…”
Section: Therapeutic Perspectives For Improving the Effects Of Fdamentioning
confidence: 99%